Product Design Improvement of Water Dispenser Tap using Triz Method - Mansor, M.R.; Shaharuzaman, M.A.; Tahir, M.M.; Akop, M.Z.; Salim, M.A.; Zainudin, A.Z. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
To produce the best solution for improving any product design that should be able to satisfy the design requirements (i.e., faster, better and cheaper), there were several stages typically involves the root cause analysis and idea generation activities. In this paper, product design improvement of a water dispenser is demonstrated using Theory of Inventive Problem Solving (TRIZ) method. The objective of this study was to find out the design solution which was able to solve the problem of water spill out that occurred after dispensing water from the dispenser tap. TRIZ Function Model and Engineering Contradiction method were used to model the problem, followed by TRIZ Contradiction Matrix and 40 Inventive Principles to generate potential solutions. The design improvement process based on the TRIZ method generated new concept design of water dispenser tap component which was able to eliminate the water spill out problem, while maintaining the existing dispensing function. In addition, the new dispenser tap conceptual design also required less component to operate compared with the existing design, hence, lowering the product cost.